2009
DOI: 10.1152/ajpcell.00428.2008
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia reprograms calcium signaling and regulates myoglobin expression

Abstract: Myoglobin is an oxygen storage molecule that is selectively expressed in cardiac and slow-twitch skeletal muscles that have a high oxygen demand. Numerous studies have implicated hypoxia in the regulation of myoglobin expression as an adaptive response to hypoxic stress. However, the details of this relationship remain undefined. In the present study, adult mice exposed to 10% oxygen for periods up to 3 wk exhibited increased myoglobin expression only in the working heart, whereas myoglobin was either diminish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
99
3
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(109 citation statements)
references
References 54 publications
5
99
3
2
Order By: Relevance
“…cies is adapted to deliver an acute stress response, in agreement with a recent study on the molecular pathways of Mb hypoxia regulation in mouse (53).…”
Section: Increased Globin Levels In Spalax Indicate a Function In Hypsupporting
confidence: 81%
“…cies is adapted to deliver an acute stress response, in agreement with a recent study on the molecular pathways of Mb hypoxia regulation in mouse (53).…”
Section: Increased Globin Levels In Spalax Indicate a Function In Hypsupporting
confidence: 81%
“…For a long time, the import of Reynafarje's findings was obscured by apparently contradictory studies showing that low oxygen pressure alone is not a sufficient stimulus for myoglobin expression. Now, Kanatous et al (5), in the article under discussion, resolve this issue by showing that during hypoxia, myoglobin is elevated in the working heart, but not in the relatively idle skeletal musculature, of mice exposed to prolonged hypoxia. They conclude from their studies that hypoxia alone does not stimulate myoglobin expression, but that hypoxia in consort with repetitive contraction, exactly the conditions obtaining in the muscles of people residing at high altitude, does stimulate myoglobin genesis.…”
mentioning
confidence: 99%
“…This sets the stage for their study of the regulation of myoglobin expression in muscle. They determine the effects of hypoxia on transcriptional regulation and expression of myoglobin both in the skeletal muscle of mice following a 3-wk acclimatization to hypoxia (10% oxygen) and in a cell culture system using myotubes, tubules of differentiated muscle cells (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The seal fetus is repeatedly exposed to hypoxia in utero, when the mother is diving (Elsner et al, 1969;Liggins et al, 1980), and this most likely triggers the expression of HIF-1 and the development of blood O 2 stores before birth. Mb expression, however, has been shown to be regulated by the calcium-calcineurin-NFAT (nuclear factor of activated T-cells) pathway (Bassel-Duby et al, 1993; Kanatous et al, 2009), which in turn is also partly triggered by hypoxia, but apparently only in combination with muscular activity, at least in mice (Kanatous et al, 2009;Wittenberg, 2009). A recent study using cultured myocytes from Weddell seals (Leptonychotes weddellii) showed that control of Mb development in these animals differs somewhat from that outlined above, in that Mb levels were found to increase in response to hypoxia (and also after lipid supplementation), even in the absence of contraction (De Miranda et al, 2012).…”
Section: Introductionmentioning
confidence: 99%